PTPN22 rs2476601 Polymorphism and Immunological Biomarkers in Systemic Lupus Erythematosus: A Case Control Study - Navami S; Prajna P Shetty; Jishamol K; Gargi R Nair (The Bioscan, 2025)
Background: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disorder characterized by immune dysregulation, loss of self-tolerance, and chronic inflammation. Genetic variants, such as the PTPN22 polymorphism (rs2476601), have been associated with altered immune signaling and increased susceptibility to autoimmune diseases, though their impact differs among ethnic groups. Identifying such single nucleotide polymorphisms (SNPs) and comparing them with serological biomarkers including anti-dsDNA antibodies, complement components (C3, C4), and inflammatory markers provides valuable insight into disease pathogenesis, helps predict disease activity, and may contribute to personalized diagnostic and prognostic approaches in SLE. Objectives: This study aimed to investigate the presence of PTPN22 rs2476601 polymorphism in SLE patients compared with healthy controls and to evaluate the relationship between genetic findings and established serological biomarkers in an Indian cohort. Methods: A total of 50 samples were collected from clinically confirmed Systemic Lupus Erythematosus (SLE) patients and age- and sex-matched healthy controls after screening more than 1,000 symptomatic individuals at Holy Cross Hospital. Serological analyses included the measurement of anti-dsDNA antibodies by (enzyme-linked immunosorbent assay, ELISA), complement component C3 (Turbidimetric immunoassay), C-reactive protein (CRP) (Latex turbidimetric immunoassay), erythrocyte sedimentation rate (ESR) (Westergren method), and serum creatinine (Biochemical assay). All statistical analyses were performed using GraphPad Prism version 7. Group comparisons were conducted to evaluate intergroup differences, and Spearman’s correlation analysis was applied to assess relationships between immunological and biochemical parameters. Results: SLE patients exhibited significantly elevated anti-dsDNA antibody levels and reduced C3 levels compared with controls (p < 0.00001). Both CRP and ESR were also significantly higher in the SLE group (p < 0.00001), while serum creatinine did not differ significantly (p > 0.05). No meaningful correlations were observed between biomarker levels and disease duration. Genotyping revealed that PTPN22 SNP-G and SNP-T alleles were more frequent among SLE patients, whereas controls predominantly carried the wild-type allele. Assay validation confirmed high specificity and reproducibility. Conclusion: The findings demonstrate that anti-dsDNA positivity and low C3 levels are reliable serological markers for SLE in this cohort, while PTPN22 rs2476601 polymorphism represents a potential genetic risk factor. Integration of biomarker profiling and genetic testing may enhance diagnostic precision and support risk stratification in SLE. Larger multi-ethnic studies are warranted to validate these results and explore their clinical utility. KEYWORDS: Systemic lupus erythematosus, PTPN22, rs2476601, anti-dsDNA, complement C3, biomarkers, qPCR, genetic susceptibility